An Innovative Consulting Group for Sharing Expertise on Launching and Sustaining Student-Run Free Clinics: A Model for Building Student-Run Endeavors - Maniar, Yash M.; Bahethi, Rohini R.; Naert, Mackenzie; Leader, Andrew M.; Thomas, David C.; Meah, Yasmin (Medical science educator, 2020)
Student-run, physician-supervised free clinics (SRFCs) provide essential healthcare services for many uninsured and underinsured patients in the USA. While SRFCs serve diverse populations and offer distinct services, they face many similar barriers to successful clinic operation. Historically, the sharing of best practices and development strategies across SRFCs has been limited and insufficient for both new and emerging free clinics. To address these challenges, in 2015, the East Harlem Health Outreach Program (EHHOP) at the Icahn School of Medicine at Mount Sinai formed the EHHOP Consulting Group (ECG), with the goal of providing client SRFCs individualized support from medical students. ECG draws from the experience of EHHOP and other veteran SRFCs to provide customized solutions to best address client SRFC needs. Here, we describe ECG’s inception, structure, and consulting work with client SRFCs. We propose that this interactive, longitudinal model can be adapted to other healthcare trainee initiatives where cross-institutional collaboration could prove beneficial.